Changes in Water Properties During the Cocoon Winding Process (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In the cocoon processing process, heating the water has a significant effect on the alkalinity, despite the dissolved substance from the cocoon casing and silkworm pupa in the cooking bath. This is because a significant portion of the alkali metal salts contained in the cocoon casing are dissolved during immersion in those stages of processing that occur at low temperatures, and the alkalinity in the working bath tends to increase. Since a large amount of water is added in the final section at low temperatures, the properties of the water in this part of the processing approach those of the original water. If water containing a high degree of alkalinity is used in the conditioning section, there is a risk of increasing the pH to very high levels.            It is preferable to keep the alkalinity low by maintaining a high temperature in this section. The water used in the decoiling operations is at a lower temperature and is therefore affected by the properties of the original water. The quality of the decoiling water is of great importance compared to the cooking process. Very little soluble matter from the cocoon shell is present in the decoiling bath, since most of it has already been dissolved in the cooking process, but there will be some soluble matter from the pupae that has not been dissolved in the cooking bath.